(untitled) (Third Sector Social Economic Review, 2025)
In this study, it was aimed to evaluate university students’ perceptions of poverty and happiness levels. Relational screening model, one of the general screening models, was used in the study. The study group of the research consisted of 510 university students continuing their education in different programs at Kırıkkale University Vocational School of Health Services. The data were collected in the period of April 2025. As data collection tools, “Personal Information Form”, “Poverty Perception Scale” and “Happiness Scale” were used to obtain information about the students and their families prepared by the researchers. In the analysis of the data, One-Way Variance Analysis and t-test were used in addition to descriptive statistics, and the Pearson Correlation Coefficient was calculated. As a result of the research, it was determined that female students, students in the 18-20 age group and students whose income is higher than their expenses have low perceptions of poverty and high levels of happiness. In addition, it was determined that there was a positive and moderately significant relationship between the students’ poverty perceptions and happiness levels, and that the program attended did not make a significant difference in the students’ poverty perceptions and happiness levels.